The Himalayan Climate and Water Atlas - Duncan J. Quincey (Mountain Research and Development, 2017)
Reviewed: The Himalayan Climate and Water Atlas Edited by Arun Bhakta Shrestha, Nand Kishor Agrawal, Björn Alfthan, Sagar Ratna Bajracharya, Judith Maréchal, and Bob van Oort. Kathmandu, Nepal, Arendal, Norway, and Oslo, Norway: International Centre for Integrated Mountain Development (ICIMOD), GRID-Arendal, and Centre for International Climate and Environmental Research - Oslo (CICERO), 2015. 96 pp. Paperback: Available on request, ISBN 978-92-9115-356-5. E-book: Free download at http://lib.icimod.org/record/31180, ISBN 978-92-9115-357-2.